Longevity of risks in software development projects: a comparative analysis with an academic environment - Alves, Luís M.; Souza, Gustavo; Ribeiro, Pedro; Machado, Ricardo J. (Procedia computer science, 2021)
The study presented in this paper was developed in an academic environment. All subjects involved in this research are enrolled in the Information Systems Master’s Degree of the University of Minho. The main objective of this study is to demonstrate the need for the continuity of studies about the risks presented in software development projects. For this purpose, we analyzed more than four hundred risks and about one hundred problems faced and documented by the working groups. With the collected data we defined a list of twenty risks and conducted a comparative study of these risks with others already formalized in previous industrial studies. The comparison data was analyzed and interpreted, and important conclusions were made.